Legal Study Of The Constitutional Court Decision Number 013-022/PUU-IV/2006 On The Case Of Insult Against The President And Vice President From The Perspective Of The National RKUHP - zulfa vikra (Vonis, 2025)
Constitutionally, the Indonesian state guarantees and respects the human rights of citizens to express opinions, speak and organize, as long as it is done in accordance with applicable laws. However, if this is done in the form of insults, especially against the President and Vice President, then it can be subject to Articles 134, 136 bis, and Article 137 of the Criminal Code. Based on the Constitutional Court Decision Number 013-022/PUU-IV/2006, the three articles were invalidated because they were considered contrary to Article 28 of the 1945 Constitution. Then the Article on insulting the President and Vice President was reappeared in the Draft National Criminal Code. The purpose of this research is to find out the regulation of insulting the President and Vice President after the Constitutional Court Decision. This research uses normative legal research, namely research on primary, secondary, and tertiary legal materials collected through literature studies. Then the data that has been collected is processed and analyzed qualitatively descriptive. The results show that the regulation of insults against the President and Vice President as stated in the Draft National Criminal Code is not contradicted by the Constitutional Court Decision Number 013- 022/PUU-IV/2006 because the legal constitution is different from Article 134, Article 136 bis, and Article 137 of the Criminal Code. Then in the concept of criminal law policy, the problem of insulting the President and Vice President must be